Pengembangan Aplikasi Edukasi Sejarah Pahlawan Nasional Berbasis Android dengan Unity Engine - Rahayu, Sri; Gumelar, Gilang (Institut Teknologi Garut, 2025)
An Android-based educational media application on Indonesian National Heroes was developed in this study using Unity Engine as the main platform. This application was developed to increase young people's interest in national history through a more interactive and modern approach. Students' low interest in history lessons is generally triggered by monotonous and unattractive teaching methods. Therefore, this application is designed to be more attractive by integrating multimedia elements (text, images, audio, video) and gamification features in the form of quizzes. The development of this application uses the MDLC method, which includes six main steps: concept planning, design, material collection, compilation, testing, and distribution. The testing process was carried out using the Alpha Testing method with a Blackbox Testing approach to ensure that the application ran according to specifications. The final results showed that the application functioned properly. It is hoped that this application can become an alternative medium for learning history that is fun, interactive, and relevant to the learning style of today's digital generation.